Strategi BUMDes Bhakti Kencana dalam Memperkuat Ketahanan Pangan Lokal di Kecamatan Pamijahan, Kabupaten Bogor - Amas Priatna, Isep; Widada, Rasyid; Harsono, Yhonanda; Febriana, Hadijah (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2025)
Abstract This study aims to analyze the strategy of the Village-Owned Enterprise (BUMDes) Bhakti Kencana in strengthening local food security in Pamijahan District, Bogor Regency. Food security is a strategic issue in village development, especially in facing the challenges of urbanization, climate change, and dependence on external food supplies. This study employs a qualitative approach using a case study method. Data collection was conducted through in-depth interviews with BUMDes managers, local farmers, and village officials, complemented by observations and document analysis. The research findings indicate that BUMDes Bhakti Kencana develops strategies based on local potential, such as empowering farmers through integrated agricultural business units, strengthening community-based food distribution, and innovating in marketing agricultural products directly to consumers. However, the implementation of these strategies still faces obstacles such as limited access to capital, managerial capacity, and institutional synergy with external parties. These findings are expected to serve as a reference for strengthening village economic institutions and formulating food security policies that are more contextual and locally based.